Autophagy and Exosomes Relationship in Cancer: Friends or Foes? - Colletti, Marta; Ceglie, Donatella; Di Giannatale, Angela; Nazio, Francesca (Frontiers in Cell and Developmental Biology, 2021)
Autophagy is an intracellular degradation process involved in the removal of proteins and damaged organelles by the formation of a double-membrane vesicle named autophagosome and degraded through fusion with lysosomes. An intricate relationship between autophagy and the endosomal and exosomal pathways can occur at different stages with important implications for normal physiology and human diseases. Recent researches have revealed that extracellular vesicles (EVs), such as exosomes, could have a cytoprotective role by inducing intracellular autophagy; on the other hand, autophagy plays a crucial role in the biogenesis and degradation of exosomes. Although the importance of these processes in cancer is well established, their interplay in tumor is only beginning to be documented. In some tumor contexts 1) autophagy and exosome-mediated release are coordinately activated, sharing the molecular machinery and regulatory mechanisms; 2) cancer cell-released exosomes impact on autophagy in recipient cells through mechanisms yet to be determined; 3) exosome-autophagy relationship could affect drug resistance and tumor microenvironment (TME). In this review, we survey emerging discoveries relevant to the exosomes and autophagy crosstalk in the context of cancer initiation, progression and recurrence. Consequently, we discuss clinical implications by targeting autophagy-exosomal pathway interaction and how this could lay a basis for the purpose of novel cancer therapeutics.